1970
DOI: 10.1002/jhet.5570070213
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of the second dissociation constants of the aminoquinolines

Abstract: The second dissociation constants representing the transition from monocation to dication for all of the isomeric aminoquinolines have been determined as pKa' values. The analogous values for 2‐ and 4‐aminopyridine have been recalculated using a revised HO scale. The accurate determination of the second pKa values follows from measurement, for the first time, of the ultraviolet spectra of all the mono‐ and dications of the aminoquinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The molar absorptivities of 1 and I1 were calculated a t each absorption maximum as well as a t each distinct vibrational band and agreed with published values (31,32). The molar absorptivities of the bound mono-cation& of I and I1 were calculated from the absorbances of solutions of the probes in which pH = pKa -2 and to which a sufficient excess of DNA was added so that further addition of DNA produced no perceptible changes in the absorption.…”
Section: ) Of the Compoundssupporting
confidence: 70%
“…The molar absorptivities of 1 and I1 were calculated a t each absorption maximum as well as a t each distinct vibrational band and agreed with published values (31,32). The molar absorptivities of the bound mono-cation& of I and I1 were calculated from the absorbances of solutions of the probes in which pH = pKa -2 and to which a sufficient excess of DNA was added so that further addition of DNA produced no perceptible changes in the absorption.…”
Section: ) Of the Compoundssupporting
confidence: 70%
“…It was previously shown that the ultraviolet spectra of the isolated dications of the aminoquinolines and aminoisoquinolines strongly resemble the quinolinium and isoquinolinium ions, respectively. 3,4 This suggests that the final site of protonation is the primary amine group of these two isomers with the second proton being added at the second ring nitrogen atom-N-l.…”
mentioning
confidence: 99%
“…Dissociation Constants of Aminoisoquinolines spread may not exceed ±0.06 units for pKa' values above zero and ±0.10 for values below zero.76 A. Albert, R Goldacre, and J. N. Phillips, J. Chem. Soc., 2240 (1948) 6. A. R Osborn, K. Schofield, and L. N.Short, ibid., 4191 (1956).…”
mentioning
confidence: 99%
“…The preparation of the mixture of lithium enolates followed the procedure described by Huff7 and was essentially similar to that previously described by other authors. 6 In a flame-dried apparatus, under nitrogen pressure, triphenyl methane was dissolved in the appropriate solvent, and to this a solution of phenyllithium in diethyl ether was added. 3-Methylcyclohexanone was then added with a syringe, and, after an appropriate length of time, the enolate mixture was quenched with excess acetic anhydride.…”
mentioning
confidence: 99%